Effect of Groove Height on Hydraulic Performance of Spiral Corrugated Firefighting Pipe - Gercham Gan; Nordin, Normayati; Mohd Sukri Ramli; Azian Hariri; Mohammed, Akmal Nizam Mohammed (International Journal of Integrated Engineering, 2026)
Corrugated pipes are recognized for their strength, flexibility, and ease of installation, making them suitable for various industries, including firefighting systems. Unlike conventional firefighting systems that typically use rigid and fixed-length pipes, corrugated pipes can be easily retrofitted, particularly in confined or irregular spaces. However, due to their complex geometry, predicting the performance of corrugated pipes remains a challenge. This study numerically investigates the hydraulic performance of spiral corrugated pipes applied in firefighting systems. It specifically examines the effect of groove height on the friction factor and flow uniformity to determine optimal design configurations. Computational Fluid Dynamics (CFD) was employed, and the RNG k-ε turbulence model was validated as the most effective, demonstrating a numerical deviation ±5%. The results demonstrate that the friction factor is notably affected by the corrugation due to the presence of secondary backflow vortices within cavities, resulting in intensified turbulence, increased flow resistance, and greater wall friction. Minimal performance disruption, however, is demonstrated for the flow uniformity as strong vortices and mixing turbulence enhance the flow homogeneity. The groove height, k/Dint= 0.015 is regarded as the most optimal, yielding a balanced hydraulic performance with an effective friction factor while maintaining flow uniformity. Overall, spiral corrugated firefighting pipes may be required due to design or structural constraints, but they could have hydraulic performance deficiencies of up to 60% compared to conventional smooth pipes.